By-product of passion fruit seed (Passiflora edulis) in the diet of commercial laying hens - Zanetti, Leonardo Henrique; Murakami, Alice Eiko; Diaz-Vargas, Mayra; Flávia Quiles Garcia Guerra, Ana; Ospina-Rojas, Ivan Camilo; Matumoto Pintro, Paula Toshimi; Cruz-Polycarpo, Valquíria Cação [UNESP] (Canadian Science Publishing, 2016)
This study evaluated the effects of the inclusion of the by-product passion fruit seed (BPFS) in the diet of laying hens on performance, blood variables, quality, and lipid oxidation in eggs. A total of 384 Hy-line W36 layers (32 wk old) were distributed in a completely randomized design, with six treatments (control, 2.5%, 5.0%, 7.5%, 10.0%, and 12.5% inclusion of BPFS), eight replicates and eight birds each. The productive performance was evaluated for three cycles of 28 d each. There was no difference (P > 0.05) in egg production and feed conversion. However, feed intake showed increased linearly (P < 0.05). The egg weight, egg mass, percentage of eggshell, eggshell thickness, and Haugh unit did not differ (P > 0.05); however, the specific gravity of eggs increased (P < 0.05). Total cholesterol and blood triglycerides decreased linearly (P < 0.05). To evaluate the lipid yolk oxidation, a 6 × 5 × 2 factorial design (six levels of BPFS × five storage periods × two temperatures) was used. There was an interaction (P < 0.05) among the levels of BPFS, time, and storage temperature with the lowest oxidation level of 12.5% when eggs were refrigerated. The BPFS can be included at a level up to 5.0% without compromising bird performance and 12.5% for egg quality, and this level reduced yolk lipid oxidation.
Keywords: By-product of fruit; Egg quality; Oxidation; Performance